Модель пульсометра на базі мікроконтроллера з інтеграцією у мобільний застосунок - Малков, Є. І. (ХНУРЕ, 2025)
The problem of monitoring heart rate and user health status was addressed in this work. It has been established that constant heart rate monitoring is necessary for effective health management, especially for people with chronic conditions or those engaged in physical activities. Ignoring heart rate fluctuations can lead to serious health consequences. One solution to this problem is the creation of a heart rate monitor based on Arduino with a user application for Android. The device collects heart rate data using a pulse sensor and transmits it to the Android application via Bluetooth. The application provides real-time monitoring, data storage, and analysis of the heart rate.
Keywords: моніторинг пульсу; апаратна платформа